2006
DOI: 10.1002/aic.11053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ultrafine carbon cryogel microspheres using a homogenizer

Abstract: in Wiley InterScience (www.interscience.wiley.com).Ultrafine carbon cryogel (UCC) microspheres of diameter <5 mm with desirable mesopores were successfully synthesized using a homogenizer during the inverse emulsion polymerization of a resorcinol-formaldehyde (RF) aqueous solution in an organic solvent as a continuous phase (CP) containing nonionic surfactant, SPAN80 as an emulsifier, followed by solvent exchange, freeze-drying, and pyrolysis in an Ar atmosphere. The curing time of RF solution before emulsific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This can be explained by the significant difference in the viscosity of the RF solution, shown in Fig. 2, which was also mentioned in previous reports [25,40]. In this study, the CV values of the Ni/CCB were below 10%, irrespective of the Ni content.…”
Section: Influence Of Processing Condition Of the Si Methodssupporting
confidence: 41%
See 1 more Smart Citation
“…This can be explained by the significant difference in the viscosity of the RF solution, shown in Fig. 2, which was also mentioned in previous reports [25,40]. In this study, the CV values of the Ni/CCB were below 10%, irrespective of the Ni content.…”
Section: Influence Of Processing Condition Of the Si Methodssupporting
confidence: 41%
“…Yamamoto et al [2] reported the synthesis of spherical carbon cryogels by the inverse emulsion polymerization of resorcinol-formaldehyde (RF) solution. Soottitantawat et al [25] succeeded in preparing ultrafine carbon cryogel microspheres by using a homogenizer during the inverse emulsion polymerization. The curing time of RF solution before emulsification significantly influenced the size of the microspheres without changing their porosity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] As carbon cryogel and aerogel microspheres possess large surface area, they have been well studied for their use as electrochemical double layer capacitors due to their enhanced double layer capacitance. [1][2][3][4][5][6][7][8][9][10][11] As carbon cryogel and aerogel microspheres possess large surface area, they have been well studied for their use as electrochemical double layer capacitors due to their enhanced double layer capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…There are, at least, four different types of materials named "cryogels": (i) gelatinous precipitate forming during cryoprecipitationblood plasma treatment upon cooling to ca. 4°C [57]; (ii) frozen polymeric or other hydrogels used 14 as antipyretic materials or materials for thermal energy storage [58]; (iii) polymeric and inorganic cryogels produced using sol-gel technology with subsequent freeze-drying including individual and mixed inorganic oxides, polymers, hybrids, composites, and carbon cryogels (the latter is prepared by carbonisation of polymeric cryogels) [59][60][61][62][63][64][65][66][67] There are many cryogels prepared from synthetic polymers such as poly(vinyl alcohol), PVA, which was one of the first polymers used in cryogel preparation [2][3][4]36,38,74,78,82]. PVA alone or in combination with other polymers or proteins is very popular material for the cryogel preparation because its structure containing the (-CH 2 -C(OH)H-) n chain allows various degrees of cross-linking with the participation of the active COH groups, different cross-linkers and co-polymers.…”
Section: Types Of Cryogel Based Composite and Hybrid Materialsmentioning
confidence: 99%